Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Agustin solved an equation as shown. What error did Agustin make? What is the correct answer?
1/3x - 4 = 3/4x + 1
12 (1/3x) - 4 = 12(3/4x) + 1
4x - 4 =9x + 1
-5 = 5x
x= -1


Sagot :

(1/3x)-3/4x=1+5
(4 1-3  3)/12x=1+4
-5/12x=5
12x=-5/5=1
x= -1/12





The error is in the second step.

This is because when you want to remove denominators you multiply by the least common multiple of them and you multiply all the equation, not only some terms of it:

[tex]12(\frac{1}{3} x - 4) = 12 (\frac{3}{4}x+ 1)[/tex]

And we can continue solving:

[tex]4x - 48 = 9x + 12 \\5x=-60\\x=\frac{-60}{5} = -12[/tex]